Optimization of drug loading methods for exosome-mimetic cell derived nanovesicles - Chan, Matthias Khar Hin (Nanyang Technological University, 2021)
Cell-derived nanovesicles (CDNs) have been recently discovered as a form of bioinspired Drug Delivery System (DDS) which are produced from exosomes. However, the loading of therapeutics into CDNs has yet to be optimised due to its recent discovery. In this study, we have evaluated the stability of the CDNs produced in different buffers over 10 days which will allow for different methods of therapeutic loading into the CDNs in the future. The CDNs produced in different buffers showed similar physical characteristics, and particle concentration as previously reported in the literature. In addition, we have evaluated the loading of Doxorubicin (DOX), which is a well-known anticancer drug, into the CDNs through remote loading. We compared the DOX loaded into CDNs made in either acidic or basic buffers whilst ensuring that the physical characteristics, protein, and particle concentration of the CDNs were still maintained before and after dialysis. Results from this part of the study suggest that the loading of DOX into the CDNs made in basic buffer was higher than that of the CDNs made in an acidic buffer. Furthermore, we also evaluated the loading of DOX into CDNs made with cholesterol through remote loading. Results reinforced that CDNs made with cholesterol did not have a marked improvement in DOX uptake using remote loading as previously reported in the literature. In summary, the results suggest that CDNs can be made in different buffers of varying pH and that remote loading of DOX into CDNs using a basic buffer is more efficient. There was insignificant difference between DOX loaded into CDNs with or without cholesterol. Further studies should be done on the release of drug from the CDNs to obtain real values of loaded DOX.